Feasible utilization of waste limestone sludge as filler in bituminous concrete - Choudhary J.; Kumar B.; Gupta A. (My University, 2025)
The dimensional limestone industries produce a substantial amount of waste limestone sludge during the polishing of stone slabs. The storage and disposal of this non-biodegradable sludge cause issues regarding environmental pollution, shortage of disposal land, increase in transportation cost, and several other associated problems. This study investigated the usability of dried limestone sludge (LS) instead of conventional stone dust (SD) as filler in bituminous concrete mixes. The performance of SD and LS incorporated mixes in several aspects was compared, and the amount of LS needed to ensure optimum bituminous mix behavior is determined. The physical and chemical properties of both fillers were initially explored. Then bituminous concrete mixes having both fillers added at four different proportions (4, 5.5, 7.0, and 8.5% by weight of aggregates) were prepared using the Marshall mix design method and their optimum bitumen contents (OBC) were determined. The performance of both mixes was studied. LS mixes displayed paramount rutting resistance, fatigue resistance, indirect tensile strength, ravelling, and resilient modulus than conventional mixes. It mostly attributed to the fine nature of LS, which ensured its better distribution. LS mixes also had lower OBC than SD mixes due to lower porosity and bitumen extender action of LS. LS displayed a good affinity towards bitumen due to calcite in its composition, which led to excellent adhesion and moisture resistance in its mixes. The test results suggested that the utilization of chosen LS as filler at an optimum filler percentage of 6.45% can result in formation of bituminous mixes with satisfactory engineering properties, lower bitumen content as well as lower greenhouse gas emissions. © 2019 Elsevier Ltd